Colloidal Synthesis of NbS2 Nanosheets: From Large-Area Ultrathin Nanosheets to Hierarchical Structures - Li, Wenhui; Wei, Xijun; Dong, Hongmei; Ou, Yingqing; Xiao, Shenghuan; Yang, Yang; Xiao, Peng; Zhang, Yunhuai (Frontiers in Chemistry, 2020)
Layered NbS2, a member of group-Ⅴ transition metal dichalcogenides, was synthesized via a colloidal synthesis method and employed as negative material for supercapacitor. The morphologies of NbS2 can be tuned from ultrathin nanosheets to hierarchical structures through dynamics control based on growth mechanism.Electrochemical energy storage measurements present that the ultrathin NbS2 electrode exhibits the highest rate capability due to the largest electrochemical surface area and efficient ion diffusion. While the hierarchical NbS2 shows the highest specific capacitance at low current densities for small charge transfer resistance, displays 221.4 F g -1 at 1 A g -1 and 117.1 F g -1 at 10 A g -1 , and cycling stability with 78.9% of the initial specific capacitance after 10000 cycles. The aggregate or stacking of nanosheets can be suppressed effectively by constructing hierarchical structure NbS2 nanosheets.